Cholera: a paradigm for understanding emergence, virulence and temporal patterns of disease - Mekalanos, John (Henry Stewart Talks, 2009)
Vibrio cholerae epidemiology and classification, Vibrio cholerae and cholera, Cholera mortality, The history of V. cholerae research, Cholera toxin and pathogenesis, Comparative genomics, The TCP Island of Vibrio cholerae, Structure of the CTX prophage, Vibrio cholerae microarray, Clinical sample analysis, Virstatin, What influences the seasonality and epidemiology of cholera?, Vibriophages, Cholera incidence as a function of environmental phage isolation and concentration, Phenotypic differences between biotypes, Types of cholera vaccines